Corporate Social Responsibility in the pharmaceutical industry - Mejia Reatiga, Camilo Antonio; Gonzalez Barranco, Saul Enrique; Torres-Saumeth, Katherine María (Estudios de Administración, 2021)
What lies ahead in the research into Corporate Social Responsibility (CSR) in the Pharmaceutical Industry? This article analyzes the topics now being studied, the types of research already undertaken and obvious gaps that have to be filled for its development. To this end, we reviewed the investigations conducted in the 2000-2020 period in the highest-impact journals (according to Journal Citation Report - JCR), through a search in Web of Science. There are various reasons for organizations to formally assume CSR; there are several definitions of the concept and there are different ways to understand it within the environment of the Pharmaceutical Industry. The need to incorporate CSR strategies and programs designed for this type of industry is generally accepted, nevertheless, the main conclusions are unfortunately that the industry still shows a superficial attitude to CSR, and on the other hand that third parties such as the State will have to become involved. The role of the consumer and the internationalization of pharmaceutical companies are also of paramount importance.